Penggunaan COBIT 2019 GMO dalam Menyusun Pengelolaan Layanan TI Prioritas pada Transformasi Digital BankCo - Bq. Dinda Tarbiyatuzzahrah; Rahmat Mulyana; Ari Fajar Santoso (Jurnal Teknologi Informasi dan Multimedia, 2023)
The rapid advancement of digital technology causes fierce competition from digital-born companies to the incumbent ones, so they need to accelerate their digital transformation (DT). Prior research has found the influence of IT governance (ITG) mechanisms on organizational performance. (OP), mediated by DT. However, there is a need to identify the prioritized IT services management initiatives to support their DT. This case study is performed in BankCo using Design Science Research (DSR) and the latest ISACA’s framework of COBIT 2019 Governance & Management Objectives (GMO). The solution and implementation roadmap results are analyzed and designed based on interviews data and documents triangulation. There are three important initiatives BankCo namely DSS05 Managed Security Service, BAI06 Managed IT Changes, and BAI04 Managed Availability and Capacity. The estimated solution implementation increased BankCo’s maturity to 3.XY. This research contributes to the knowledge base regarding IT service management prioritization and provides practical implications for BankCo to enhance their DT, and the banking industry in general.